A soxRS-Constitutive Mutation Contributing to Antibiotic Resistance in a Clinical Isolate of Salmonella enterica (Serovar Typhimurium) - Koutsolioutsou, Anastasia (American Society for Microbiology, 2001)
The soxRS regulon is activated by redox-cycling drugs such as paraquat and by nitric oxide. The >15 genes of this system provide resistance to both oxidants and multiple antibiotics. An association between clinical quinolone resistance and elevated expression of the soxRS regulon has been observed in Escherichia coli, but this association has not been explored for other enteropathogenic bacteria. Here we describe a soxRS-constitutive mutation in a clinical strain of Salmonella enterica (serovar Typhimurium) that arose with the development of resistance to quinolones during treatment. The elevated quinolone resistance in this strain derived from a point mutation in the soxR gene and could be suppressed in trans by multicopy wild-type soxRS. Multiple-antibiotic resistance was also transferred to a laboratory strain of S. enterica by introducing the cloned mutant soxR gene from the clinical strain. The results show that constitutive expression of soxRS can contribute to antibiotic resistance in clinically relevant S. enterica.